1990
DOI: 10.1002/1097-0142(19900501)63:9<1657::aid-cncr2820630902>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Results of the United Kingdom children's cancer study group's malignant germ cell tumor studies

Abstract: The United Kingdom Children's Cancer Study Group's malignant germ cell tumor studies were undertaken to establish standard protocols for investigating, staging, and treating children, and to study the efficacy of new drug combinations and the value of serial measurement of serum alphafetoprotein (AFP) and human chorionic gonadotrophin (HCG). Boys with Stage I testicular tumors were treated by orchidectomy alone, whereas, after appropriate surgery, chemotherapy was recommended for children with more advanced te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
72
0
7

Year Published

1990
1990
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(83 citation statements)
references
References 36 publications
4
72
0
7
Order By: Relevance
“…[5][6][7][8][9]38,39 Significant concerns regarding the longterm toxicity of cisplatin and bleomycin [11][12][13][14][15] delayed the introduction of cisplatin-based therapy in pediatric patients. After pediatric Phase II studies suggesting that high-dose cisplatin was effective and tolerable in patients with solid tumors and neuroblastoma, 23,24 the POG/CCG Intergroup Germ-Cell Tumor Subcommittee designed a randomized study to evaluate the effect of cisplatin dose intensity on outcome.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…[5][6][7][8][9]38,39 Significant concerns regarding the longterm toxicity of cisplatin and bleomycin [11][12][13][14][15] delayed the introduction of cisplatin-based therapy in pediatric patients. After pediatric Phase II studies suggesting that high-dose cisplatin was effective and tolerable in patients with solid tumors and neuroblastoma, 23,24 the POG/CCG Intergroup Germ-Cell Tumor Subcommittee designed a randomized study to evaluate the effect of cisplatin dose intensity on outcome.…”
Section: Discussionmentioning
confidence: 85%
“…6 -9 Although small pediatric trials suggested cisplatin-based therapy was efficacious, 10 there were significant concerns regarding the long-term toxicity of this agent in young children. [11][12][13][14][15] Based on these concerns, several pediatric investigators evaluated the use of other strategies to eliminate the toxicity associated with cisplatin. Mann et al 16 evaluated the use of carboplatin, etoposide, and bleomycin (JEB) in pediatric patients with malignant GCT and reported a 5-year event-free survival (EFS) of 87.8%.…”
mentioning
confidence: 99%
“…The role of chemotherapy in ovarian tumours during the first half of the study period has been previously described (La Vecchia et al, 1983). The improvements in more recent years were parallel with those in the UKCCSG germ-cell tumour studies (Mann et al, 1989), in which many of the children analysed here were entered.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, germ cell malignancies arising from extragonadal primary site represent nearly 50 -60% of all GCTs in children . Extragonadal primary location coupled with high serum levels of alpha-fetoprotein (AFP) (more than 10 000 ng ml À1 ) at diagnosis are the most unfavourable prognostic factors for these children (Mann et al, 1989;Marina et al, 1992;Baranzelli et al, 1999Baranzelli et al, , 2000Schneider et al, 2000;Lo Curto et al, 2003). Moreover, the prognosis of extragonadal GCT is significantly influenced by the histological differentiation, with the secreting GCTs (embryonal carcinoma, yolk sac tumour, choriocarcinoma) and immature teratoma having a higher risk of relapse after primary treatment than germinoma/dysgerminoma and mature teratoma .…”
mentioning
confidence: 99%